Engineering Metalloprotein Functions in Designed and Native Scaffolds. Issue 12 (December 2019) - Nastri, Flavia; D'Alonzo, Daniele; Leone, Linda; Zambrano, Gerardo; Pavone, Vincenzo; Lombardi, Angela
Abstract : Metalloproteins are crucial for life. The mutual relationship between metal ions and proteins makes metalloproteins able to accomplish key processes in biological systems, often very difficult to reproduce with inorganic coordination compounds under mild conditions. Taking inspiration from nature, many efforts have been devoted to developing artificial molecules as metalloprotein mimics. We have witnessed an explosion of protein design strategies leading to designed metalloproteins, ranging from stable structures to functional molecules. This review illustrates the most recent results for inserting metalloprotein functions in designed and engineered protein scaffolds. The selected examples highlight the potential of different approaches for the construction of artificial molecules capable of simulating and even overcoming the features of natural metalloproteins. Highlights: Developing artificial metalloproteins represents a valuable approach for understanding at the molecular level how nature tunes the metal center reactivity, thus producing functional diversity. The field of protein design and engineering has progressed spectacularly in the past decades. Starting from the construction of simple structural mimics, insertion of further levels of complexity (such as second-shell interactions) enables fine-tuning and expansion of activities in artificial metalloproteins. Currently, a variety of functions are being implanted into peptide/protein scaffolds, thus producing artificial catalysts, competent under environmentally benign conditions and with high turnovers. By joining the power of different and complementary strategies, designers can shape the protein scaffold and optimize and/or repurpose the metalloprotein function, toward demanding needs.